ANALYSIS OF EFFORTS TO REDUCE THE NUMBER OF REJECTED BEVERAGE PRODUCT BOTTLES IN THE ASEPTIC PACKAGING DEPARTMENT AT PT XYZ USING THE SIX SIGMA AND PDCA METHODS - agung (Journal Knowledge Industrial Engineering (JKIE), 2024)
The number of requests for packaged beverage products, especially in the Pasuruan Regency area, is increasing. This is what triggers the growth of manufacturing companies in the beverage industry. One of them is PT XYZ, which is a bottled beverage industry manufacturing company in the Pasuruan Regency area. Meanwhile, PT Six Sigma method with DMAIC and PDCA (plan, do, check, action) is considered capable of overcoming these obstacles. This study aims to improve or repair one part of the machine, namely Scrapper in order to reduce the number of defective bottles. The material used in the repair is Teflon.